Analisis Semiotika Makna Kesepian Dari Lirik Lagu ‘Kota Ini Tak Sama Tanpamu’ Karya Nadifh Basalamah - Julaeha (AN-NASHIHA Journal of Broadcasting and Islamic Communication Studies, 2026)
This study aims to analyze the representation of loneliness in the song lyrics of "Kota Ini Tak Sama Tanpamu" by Nadhif Basalamah using Roland Barthes' semiotic approach. A qualitative descriptive method was employed, with analysis conducted across three layers of meaning: denotation, connotation, and myth. The object of analysis was focused on three lyric excerpts selected purposively based on thematic relevance, symbolic density, and cultural representation. The findings indicate that loneliness is represented in multiple layers: at the denotative level, it is depicted through the changing atmosphere of the city, a longing for emotional fulfillment, and a redefinition of home as togetherness; at the connotative level, the three lyrics collectively construct loneliness as a profound emotional loss; while at the mythological level, the song naturalizes the ideology that happiness and meaning in life depend on the presence of another person. This study concludes that song lyrics do not merely function as entertainment, but also as symbolic communication that reflects and reinforces social constructions of loneliness in modern life.